Chinese student mobility, local engagement and transformation of Chinese communities in England: an empirical study - Wu, Bin (Edward Elgar Publishing Limited, 2016)
Unprecedented growth and circulation of Chinese international students cannot be fully understood unless the roles of host societies including diaspora Chinese communities are taken into account. This chapter draws attention to a phenomenon of local engagement, a process of interconnections and interactions between Chinese students and local communities, leading to a co-development of both Chinese students and diaspora Chinese communities in host countries. The links and impacts of Chinese student mobility in local communities can be seen from the landscape change of Chinese communities in England since the 21st century. Accordingly, this chapter aims to address two questions: Why is local engagement important for Chinese student development in destinations? What are the impacts on the development and transformation of diaspora Chinese communities? Empirical evidence are based upon the combination of official data sources (UK Census and higher education statistics)analysis and a questionnaire survey conducted on Nottingham’s Chinese community. Policy implications for global talent training and co-development with diaspora Chinese communities are discussed.